Efficient and selective capture of uranium by polyethyleneimine-modified chitosan composite microspheres from radioactive nuclear waste. (1st January 2023) - Huang, Mengnan; Xie, Lisha; Wang, Yuejiao; Feng, Xiaogeng; Gao, Jing; Lou, Zhenning; Xiong, Ying
Abstract: Uranium extraction from radioactive nuclear waste is vital for sustainable energy supply and ecological security. Herein, a polyethyleneimine-chitosan composite microspheres n-PEI/ECH-CTS (n = 0.1, 0.2, 0.3, 0.4, 0.5) were synthetized for efficient and selective uranium adsorption. The prepared chitosan microspheres with uniform size, uniform dispersion and good mechanical strength combine cost-effectiveness and environmental benefits. The 0.4-PEI/ECH-CTS exhibits the highest adsorption capacity of 380.65 mg g −1 within only 4 h due to high nitrogen content of 6.57 mol kg −1 . The DFT calculations confirms that the optimal coordination mode of UO2 2+ and 0.4-PEI/ECH-CTS is one UO2 2+ chelated with two –NH2 from two adsorption units, respectively. Adsorption efficiency of U(VI) from simulated nuclear wastewater achieves to 100%, and the K d value is up to 1.1 × 10 4  mL g −1, which is 1.7 × 10 4 –6.1 × 10 4 times that of coexisting ions. The C U(VI) reduces in simulated wastewater from 10.98 mg L −1 to 1 μg L −1, which is well below the US Environmental Protection Agency uranium limits for drinking water (30 μg L −1 ). Besides, 0.4-PEI/ECH-CTS still maintains above 95% adsorption efficiency after seven cycles. In short, the 0.4-PEI/ECH-CTS microspheres integrate high performance, practicality and cost-effectiveness, which has great advantages in practical industrial applications. Graphical abstract: Image 1 Highlights: A PEI-modified CTS microsphere with particle size of 90–110 μm is prepared. The KdU(VI) is 1.7 × 104–6.1 × 104 times that of Ni, Co, Gd, Pr, Ce and La. 0.4-PEI/ECH-CTS is still above 95% adsorption efficiency after seven cycles. Reduce the CU(VI) from 11 mg L-1 to 1 μg L-1 to meet drinking water standard. The optimal coordination mode is one UO22+ chelated with two -NH2.